2016
DOI: 10.1109/tro.2015.2513745
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Diversity-Assisted Wireless Communication for Mobile Robots

Abstract: Abstract-Mobile robots, that wish to communicate wirelessly, often suffer from fading channels. They need to devise an energy efficient strategy to search for a high channel gain position in a near vicinity from which to begin communications. Such a strategy has recently been introduced through the Mobility Diversity with Multi-Threshold Algorithm (MDMTA). In this paper, we establish the theoretical framework for a generalized version of the MDMTA. This allows improved wireless communications in fading channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…Nevertheless, it has been shown that we can by controlling the position of the robot we can compensate small-scale fading [17]- [?]. This class of techniques have been referred to as mobility diversity algorithms [21], spatial diversity [15], jittery movements [19] among other names. In this article we will refer to this class of techniques as mobility diversity algorithms (MDAs).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, it has been shown that we can by controlling the position of the robot we can compensate small-scale fading [17]- [?]. This class of techniques have been referred to as mobility diversity algorithms [21], spatial diversity [15], jittery movements [19] among other names. In this article we will refer to this class of techniques as mobility diversity algorithms (MDAs).…”
mentioning
confidence: 99%
“…That configuration for the explored points provides five statistically independent wireless channels. Finally in [21] we presented a technique to calculate the optimum position of the points in order to maximize the expected value of the channel channel gain obtained while minimizing the amount of mechanical energy used in motion during the MDA execution.…”
mentioning
confidence: 99%
See 3 more Smart Citations